A study on inventory management at a manufacturing company - Nur Nadira, Othman (2014)
A good inventory management will always give a competitive edge to the business environment, regardless of its nature. Inventory management also plays a very important role on improving the warehouse operation. Thus, with the effective and good inventory management, the operation in the Warehouse can be improved and the operating cost can also be signiﬁcantly reduced. This research will look into the issues arise as a result of poor inventory management. In this research, Kanban system will be proposed to a manufacturing company. Primary and secondary data of raw materials were used to analyze the data collected. The weights of the raw materials were calculated to forecast the usage for a month. The Kanban card will be applied to schedule the ﬂow of operation. The production people must follow the Kanban schedule and prepare to order raw materials if the stocks of raw materials reduces. First-in First-out (FIFO) also should be implemented to make sure the product movement becomes more smooth and efﬁcient than before. From the result of this study, we will know whether the suggestion that had been proposed by the researcher to improve the inventory management system in the Warehouse success or not. Therefore, the author hopes this research will help the manufacturing company to have effective inventory management